Nazwy sekwatywne w Słowniku języka polskiego Samuela Bogumiła Lindego nienotowane w Słowniku polszczyzny XVI wieku - Michalska-Górecka, Paulina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article aims to discuss the names of Reformation-related religious dissenters included in Samuel Bogumił Linde’s Słownik języka polskiego (Polish language dictionary) which are not listed in Słownik polszczyzny XVI wieku (16th-century Polish language dictionary). The analysis of the material shows that Linde’s dictionary is a valuable, multi-layer complement to the sixteenth-century vocabulary listed in Słownik polszczyzny XVI wieku in the area of names of Reformation-related religious dissenters. First, Linde records sixteenth-century vocabulary related to the religious fractions of the time that is missing from Słownik polszczyzny XVI wieku even though it was in use at the time. Importantly, whenever he provides the source of a given lexeme, it is rarely from the sixteenth century. The lexicon also includes feminine forms of believers missing from Słownik polszczyzny XVI wieku that originated from the masculine forms listed in both dictionaries. Finally, Linde’s work presents the evolution of each religion and the emergence of new fractions, especially in the Orthodox Church and post-Reformation churches, hence it includes the names of believers of religions that emerged after the sixteenth century.